A randomized study investigating the safety, tolerability, and pharmacokinetics of evinacumab, an ANGPTL3 inhibitor, in healthy Japanese and Caucasian subjects - Harada-Shiba, Mariko; Ali, Shazia; Gipe, Daniel A.; Gasparino, Evelyn; Son, Vladimir; Zhang, Yi; Pordy, Robert; Catapano, Alberico L. (Atherosclerosis, 2020)
Evinacumab, an angiopoietin-like protein 3 monoclonal antibody, reduced low-density lipoprotein cholesterol (LDL-C) significantly in a Phase 2 study of patients with homozygous familial hypercholesterolemia. In this double-blind, placebo-controlled Phase 1 study, we compared safety, tolerability, pharmacokinetics, and pharmacodynamics of evinacumab between healthy Japanese and Caucasian adults. Subjects with LDL-C ≥2.6 and <4.1 mmol/L were enrolled to one of four dose cohorts: evinacumab subcutaneous (SC) 300 mg single dose, SC 300 mg once weekly for eight doses, intravenous (IV) 5 mg/kg, or IV 15 mg/kg once every 4 weeks for two doses. Each cohort comprised 24 subjects (12 Japanese; 12 Caucasian), randomized (3:1) to receive evinacumab or placebo within each ethnic group with a 24-week follow-up. The safety profile of evinacumab (IV and SC) in both ethnicities was comparable with placebo, with no serious or severe treatment-emergent adverse events. Pharmacokinetic profiles were comparable between Japanese and Caucasian subjects across IV and SC groups. Mean calculated LDL-C decreased from baseline with both IV doses, beginning on day 3 up to week 8. Triglyceride changes observed with evinacumab IV were rapid (seen by day 2) and sustained up to week 8. Evinacumab SC doses also reduced LDL-C and triglyceride levels, although lower doses induced smaller changes. Evinacumab (IV and SC) reduced other lipids, including apolipoprotein B, versus placebo. In both ethnicities, evinacumab (IV and SC) was generally well tolerated, exhibiting comparable pharmacokinetic profiles. Dose-related reductions in LDL-C and triglycerides were observed with evinacumab in both ethnic groups. [Display omitted] •The effects of evinacumab were compared between Japanese and Caucasian subjects.•Evinacumab exhibited a safety profile comparable to placebo in both ethnicities.•Evinacumab decreased LDL-C and triglyceride levels in both ethnicities.•Identical evinacumab doses are appropriate in both ethnicities due to similar PK/PD.•Evinacumab may help address the unmet need for LDL-C-lowering therapies in homozygous familial hypercholesterolemia (HoFH).